PEMBERDAYAAN GURU, STAF DAN ORANG TUA KB TK KHADIJAH DALAM PERTOLONGAN PERTAMA PADA KECELAKAAN DENGAN PELATIHAN BLS DAN AMBULASI - Erna Dwi Wahyuni; Ninuk Dian Kurniawati; Nadia Rohmatul Laily; Yulis Setiya Dewi; Arina Qona'ah (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2020)
AbstrakThe jurisdiction of Polrestabes Surabaya was ranked in the top 3 contributors to the number of traffic accidents of 39 Polres in the East Java Regional Police in 2017. KB Khadijah Kindergarten is in the middle of Surabaya and an area with heavy traffic, so there is a high risk of traffic accidents, but the school has never received material and information about first aid in an accident so that if there is an accident the teacher and staf are not ready and unable to provide help properly. The purpose of this community service is to provide knowledge and abilities to teachers, staff, and parents to be able to do first aid in an accident. The method used in this empowerment is lectures and demonstrations about first aid in accidents which include Basic Life Support (BLS), splinting & Bandaging, and ambulation/transportation and also using leaflet media. As many as 47 people consisting of teachers, staf and parents participated in this activity and also carried out an evaluation of knowledge and self efficacythrough pre-test and post-test. The results achieved through this activity is that there is an increase in knowledge and self-efficacy in conducting first aid in an accident. This is because the lecture, simulation, and also leaflet methods can provide a technically clear description so that participants know and can practice relief assistance in accidents. Subsequent community service activities are expected to achieve wider goals and diverse communities.